Approbation of the Algorithm of Construction of Criteria of Similarity of a Physical Process to A Technical Problem - Kravets, V.; Kolosov, D.; Kravets, V l; Shamakhanov, Vladyslav (Transactions on Engineering and Computing Sciences, 2024)
The developed general algorithm for constructing a set of similarity criteria of a physical process is applied to the technical problem of measuring the thickness of a layer of material transported along a linear conveyor line. Following the algorithm and using chain diagrams, the corresponding set of systems of linear algebraic equations with respect to homogeneity indices is found. Excluding degenerate and equivalent systems of equations, the set of basic similarity criteria consisting of two equal half-sets of direct and inverse criteria is found. Derived similarity criteria are determined by the basic criteria using the Cayley tables. The obtained set of similarity criteria includes known results.